Effect of core training on speed, quickness and agility in young male football players - Doganay, M.; Bingül, B. M.; Álvarez-García, C. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Core training effectively improves sport performance. The purpose of this study was to determine the effect of core training on the performance measures of speed, agility and quickness of U19 male football players. METHODS: A total of 24 young male football players were divided into 12 in the experimental group (aged 18.17±0.72) and 12 in the control group (aged 18.31±0.75). The experimental group performed 30-35 min core training three days a week for eight weeks while the control group continued their routine training. Measurements included a 40-meter sprint test for speed, a hexagon test for quickness and an agility-T test for agility. Pre-test measurements at the start of the study and post-test measurements after eight weeks were compared by an ANOVA 2×2. A significant level of P<0.05 was established. RESULTS: In the experimental group, there were an improvement in quickness (pre: 17.27±3.24"; post: 16.79±3.09"; P=0.005, Eta²=0.53) and agility (pre: 12.86±1.17"; post: 12.38±1.12"; P=0.003, Eta²=0.56), but the speed did not change (pre: 6.14±0.57"; post: 6.00±0.45", P=0.653). CONCLUSIONS: The use of core training in combination with normal football training is shown to be effective in improving quickness and agility but not speed among young male football players after a period of eight weeks. So, it appears reasonable to include specific core training programs within football training.